2022
DOI: 10.1002/rev3.3343
|View full text |Cite
|
Sign up to set email alerts
|

Coaching early childhood teachers: A systematic review of its effects on teacher instruction and child development

Abstract: Coaching is proven to be an effective strategy of professional development; however, rare research has documented the nuances of coaching effects and the enablers in early childhood education. This study presents a systematic review of 33 randomised controlled trials or (quasi‐)experiments to investigate the effects of coaching as a professional development tool on early childhood teachers' instruction and young children's developmental outcomes. The synthesis of evidence revealed positive effects of coaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 80 publications
0
1
0
1
Order By: Relevance
“…greater feedback, reflection with the researcher) align with the evidence-based strategies of performance feedback and coaching (e.g. Barton et al, 2011; Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…greater feedback, reflection with the researcher) align with the evidence-based strategies of performance feedback and coaching (e.g. Barton et al, 2011; Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…Selain itu, Liu et al, (2018) menemukan bahwa hampir semua sekolah PAUD di Chongging Cina tidak memiliki ahli gizi serta tenaga kesehatan lainnya sehingga kesehatan dan gizi anak ditangani oleh guru. Guru dapat melakukan pemantauan tumbuh kembang anak secara berkala setiap enam bulan sampai anak berusia enam tahun dan setiap satu tahun pada tahuntahun berikutnya (Yang et al, 2022). Hasil pengukuran tersebut dapat menjadi tolak ukur pertumbuan anak sudah sesuai atau perlu intervensi sesuai pedoman kesehatan.…”
Section: Pendahuluanunclassified
“…In addition, Thielecke et al [16] have shown that telephone coaching prevents depression in farmers. Non-face-to-face coaching has also proven effective for traditional coaches and clients, and it is helpful in teachers' professional development relating to children's education [17].…”
Section: Introductionmentioning
confidence: 99%